(3QSGdI GdENhGf ef Cgd Gdabg hMedg GdbQBfs - (3Ydj Hf ejehf Hf CHj HcQ Hf jhSa GdgGTej GdMSfj GdEOQjSj GdaGSj GdeZQHj, GHf ejehf , CHh GdMSf,J (B917 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hHYO jbhd GdYHO Ydi Hf ejehf aVGFdgG ef GdbQGA hGdabgGA hEdi GdhYGX s
(3BNQgG (B:s
( (3ZjQ hGVMg ai GdJUhjQ (B) s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hgj Ydi SHYI aUhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B27 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B251 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B741s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs